Land Suitability for Crop Curly Red Chili ( capsicum annum . L ) in Solok district Gumanti valley - Nopiardi, Rio; Dasrizal, Dasrizal; Thesiwati, Aslan Sari (STKIP PGRI Sumbar, 2013)
This research was conducted with the aim of knowing the terrain and land form units in planting curly red chili (Capsicum annum. L), knowing the characteristics of climate (temperature, humidity and rain fall), soil (pH, drainage, texture, and organic matter) and geomorphology land (altitude and slope) on the use of land for curly red pepper (Capsicum annum. L) and determine the level of suitability for curly red pepper (Capsicum annum. L).Landform unit number of research areas are 8 types of landform units and samples were taken only 4 units alone landform. Stratified random sampling based on sampling. The method used is descriptive research that perform descriptive date are then compared to the others to get a conclusion.The results showed that: daearah landforms landform origins research consists of fluvial processes with unit fluvial landforms plains, natural levees, fluvial terraces, flood plains and the origin of volcanic landforms with volcanic plateau land form units, down volcanic slopes, volcanic hills and slopes amid volcanic. Characteristics of curly red chili crop land are factors supporting and inhibiting factors. Among which the samples V1 / volcanic plains, V2 / down volcanic slopes and F1 / fluvial plains with obstacle altitude (elevation), while the sample V3 / volcanic hills with altitude inhibiting factor and slope. The suitability of land for curly red chili crop in each sample were categorized landform units at an appropriate level of suitability of land for all landform units represent the sample area